PENGARUH KONSENTRASI INHIBITOR KOROSI EKSTRAK KULIT PISANG KEPOK (Musa paradisiaca L) TERHADAP LAJU KOROSI BAJA KARBON API 5L PADA SUHU PERENDAMAN 40OC DAN 80OC - Titan Nurahman; Ediman Ginting Suka; Leni Rumiyanti (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Abstract. Research has been carried out on the effect of the concentration of Kepok banana peel extract as an inhibitor on API 5L carbon steel in 3% NaCl corrosive medium. API 5L carbon steel immersion was carried out for 7 hours with two variations of immersion temperature, namely 40 and 80 oC and five variations in the concentration of corrosion inhibitors, namely 0%, 2%, 4%, 6%, 8%. Corrosion rate testing was carried out using the weight loss method. The results showed that the largest corrosion rates at immersion temperatures of 40 and 80 oC were at 0% inhibitor concentrations, namely 60.91 mm / y and 86.91 mm / y. Meanwhile, the lowest corrosion rate was at the inhibitor concentration of 8% at immersion temperatures of 40 and 80 oC, namely 32.51 mm / y and 63.92 mm / y. The greatest effectiveness of corrosion inhibitors occurred at a concentration of 8% at immersion temperatures of 40 and 80 oC of 56.63%, and 26.44%. The results of the X-Ray Diffraction (XRD) characterization showed that the phase formed was pure Fe. Scanning Electron Microscopy (SEM) characterization showed uneven clusters and smaller size, holes and cracks were also less in 8% inhibitor at immersion temperature of 40 and 80 oC compared to inhibitor 0% at immersion temperature 40 and 80 oC.